A retrospective observational study on maternal and neonatal outcomes of COVID-19: Does the mild SARS-CoV-2 infection affect the outcome? - Li,Jing; Li,Xiang; Ye,Peiying; You,Yun; Wang,Yu; Zhang,Jing; Zhao,Weihua; Yu,Zhiying; Yao,Runsi; Tang,Jie (PeerJ, 2023)
Background Currently, several SARS-CoV-2 variants, including Omicron, are still circulating globally. This underscores the necessity for a comprehensive understanding of their impact on obstetric and neonatal outcomes in pregnant women, even in cases of mild infection. Methods We conducted a retrospective, single-center observational study to investigate the association between gestational SARS-CoV-2 infection and maternal-fetal outcomes in the Chinese population. The study enrolled 311 pregnant patients with SARS-CoV-2 infection (exposure group) and 205 uninfected pregnant patients (control group). We scrutinized the hospital records to collect data on demographics, clinical characteristics, and maternal and neonatal outcomes for subsequently comparison. Results Similar characteristics were observed in both groups, including maternal age, height, BMI, gravidity, parity, and comorbidities (p > 0.05). A majority (97.4%) of pregnant women in the exposure group with COVID-19 experienced mild clinical symptoms, with fever (86.5%) and cough (74.3%) as the primary symptoms. The exposure group exhibited significantly higher incidences of cesarean section and fetal distress compared to the control group (p < 0.05). Furthermore, pregnant women in the exposure group showed reduced levels of hemoglobin and high-sensitivity C-reactive protein, while experiencing significantly increased levels of lymphocytes, prothrombin time, alanine aminotransferase, and aspartate aminotransferase (p < 0.05). Notably, recent SARS-CoV-2 infection prior to delivery appeared to have an adverse impact on liver function, blood and coagulation levels in pregnant women. When comparing the two groups, there were no significant differences in the postpartum hemorrhage rate, premature birth rate, birth weight, neonatal asphyxia rate, neonatal department transfer rate, and neonatal pneumonia incidence. Conclusions Our study suggests that mild COVID-19 infection during pregnancy does not have detrimental effects on maternal and neonatal outcomes. However, the increased risks of events such as fetal distress and cesarean section, coupled with potential alterations in physical function, reveal the consequences of SARS-CoV-2 infection during pregnancy, even in mild cases. These findings emphasize the importance of proactive management and monitoring of pregnant individuals with COVID-19.
Keywords: COVID-19; Pregnancy; Maternal and neonatal outcomes; SARS-CoV-2